STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN KARAKTER KEPEDULIAN SOSIAL PADA PESERTA DIDIK - Andi Baso, Hamlam; Lisnawati, Sri Dewi; Atika, Nur Hikmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2021)
This study discusses the strategy of Islamic religious education teachers in instilling the character of social care in students at SMA Negeri 3 Palu. The main problem of this study is how the strategy of Islamic religious education teachers in instilling the character of social care in students at SMA Negeri 3 Palu. This study uses qualitative methods, data collection techniques through observation, interviews, and documentation. Sources of research data are primary and secondary data. The data were analyzed using data reduction, data presentation, and conclusion drawing. The results of this study indicate that the strategy of Islamic religious education teachers in instilling the character of social awareness in SMA Negeri 3 Palu has been carried out well by implementing group work strategies, understanding religious values ​​through religious activities carried out by schools, exemplary, habituation, giving sanction or punishment. the implementation of these strategies and produces religious values ​​and the character of social care between fellow students and the social environment. This strategy can help in the formation of social awareness characteristics of students to apply discipline in schools and in the surrounding environment. This can be seen from students accustomed to socializing and learning together outside the classroom, the teacher informs and gives good examples to students, such as when the bell rings indicating worship time, the teacher sets a good example by guiding students to their respective places of worship and implementing it the congregation will have a positive impact on the next level, namely the family and community environment.